Digital citizenship and redefining political participation in Turkey: The case of change.org - Demirkaya, Öznur (My University, 2018)
21st century has been characterized by the rapid developments in the information and communication technologies which have left their marks in almost every sphere of life, one of them being politics. The introduction of online and digital facilities has changed the classical understanding of citizen-state relationship as well as the scope of political participation worldwide, especially in the democratic countries. While participation has been claimed to show decline in the traditional sense with the masses being alienated from politics, the repertoire of political participation has been observed to enlarge with the introduction of unconventional, non-governmental, online and digital practices. Besides, citizenship has been redefined with such labels as “global”, “neo-republican”, “actualizing” or “democratic” citizenship due to the changing citizenship perceptions and participation tendencies of the new generations. Moreover, as a result of the increasing number of online facilities for civil procedures and activism, the digital citizenship concept has also been proposed to explain the online presence of citizens. At this point, change.org has arisen as a powerful platform that attracts digital citizens and fill a bureaucratic void for online participation -specifically mass petition campaign-. Therefore, this thesis was written to find out if there has been shift caused by the prevalence of online and digital tools in the practice of political participation and citizenship. Accordingly, semi-structured interviews were conducted with 20 Turkish change.org campaigners between February 2017 and February 2018. The analysis of these interviews contributes to the current literature in the field of politics by shedding light into the current condition of citizenship and political participation of the Turkish change.org campaigners.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Citizenship; Digital citizenship; Political participation; Change.org; Online petition campaigns